The Revolution of Abu Rakwah Against The Fatimids In Cyrenaica And His Attempt to Overthrow Their Rule in Egypt (395-397 H / 1004-1006 AD) - Ramdan Alahmar, Ramdan. M.; Abdul Hamid, Ahmad Faisal (Journal Al-Muqaddimah, 2019)
The Cyrenaica region adjacent to Egypt, which currently occupies the eastern state of Libya contemporary - at great importance in Central Islamic eras. Wherefore the Fatimids interested to control of it since the establishment of their state in the Islamic Maghreb, the year 297 AH / 909 AD. When their departure to Morocco in 361 AH / 971 AD, for stability in Egypt, they maintained on survival of the Cyrenaica region under their direct management, Because of their geographical and strategic importance of their state in Egypt. It did not pass long time until the revolution against the Fatimids in Cyrenaica lasted for two years (395-397 AH / 1004-1006 AD), Led by a man nicknamed Abu Rakwah, Attributed himself to the Umayyads Andalusia. Was able to defeat the Fatimid armies, and drop their judgment at Cyrenaica and an admin and invade Egypt to seize their king there. However, the Fatimids succeeded in his defeat and the elimination of his revolution after great efforts and huge preparations and many expenses exhausted the state treasury in Egypt. It was for this revolution after its expiry of political, social, and economic results in terms of Cyrenaica region affected on his future thereafter.